2000
DOI: 10.1017/s0376892900000035
|View full text |Cite
|
Sign up to set email alerts
|

Effect of experimental trampling and off-road motorcycle traffic on soil and vegetation of stabilized coastal dunes, Israel

Abstract: Coastal sand dunes are considered to be amongst the most fragile natural systems, however they may be subject to high-intensity recreational stresses. The aim of this study was to assess the response of soil and annual plants of stabilized Mediterranean coastal dunes in Israel to various short-duration pedestrian and motorcycle traffic intensities. A standard experimental procedure was used comprising of 0, 50, 100, 300 and 500 pedestrian passes, and 0, 20, 50, 100, 200 straight and 150 turn motorcycle passes.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
45
2
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(50 citation statements)
references
References 22 publications
1
45
2
2
Order By: Relevance
“…Path characteristics and erosion, Study Area A, before installation of pavers , was estimated for the sandy, low-angle pathway at the northern end of the dune (Path 7), where any walker-generated sand movement down the gentle slope was countered by onshore winds blowing sand back from the beach. These results from the reconstructed dune at Study Site A contrast with those from levelled dune topography in Israel, where experiments involving trampling and vehicular traffic indicated that herbaceous Mediterranean vegetation was relatively resistant to heavy recreational pressure (Kutiel et al, 2000).…”
Section: Pathway Erosion At Study Site Acontrasting
confidence: 78%
“…Path characteristics and erosion, Study Area A, before installation of pavers , was estimated for the sandy, low-angle pathway at the northern end of the dune (Path 7), where any walker-generated sand movement down the gentle slope was countered by onshore winds blowing sand back from the beach. These results from the reconstructed dune at Study Site A contrast with those from levelled dune topography in Israel, where experiments involving trampling and vehicular traffic indicated that herbaceous Mediterranean vegetation was relatively resistant to heavy recreational pressure (Kutiel et al, 2000).…”
Section: Pathway Erosion At Study Site Acontrasting
confidence: 78%
“…Dirt bikes have an immediate, temporary impact on vegetation cover, species diversity and soil compaction (Liddle 1997, Kutiel et al 2000. Longer-term impacts include soil compaction and erosion (Priskin 2003), soil loss and structural change (Goossens and Buck 2009), and a reduction in fauna and flora abundance and/or diversity, either by direct impact collision, or due to habitat destruction (Moss andMcPhee, 2006, Groom et al 2007).…”
Section: Motorised Extreme Sportsmentioning
confidence: 99%
“…Longer-term impacts include soil compaction and erosion (Priskin 2003), soil loss and structural change (Goossens and Buck 2009), and a reduction in fauna and flora abundance and/or diversity, either by direct impact collision, or due to habitat destruction (Moss andMcPhee, 2006, Groom et al 2007). Even at low intensity, impacts are higher than caused by walkers (Kutiel et al 2000), and similar to 4WDvehicles (Shaw andDiersing 1990, Rickard et al 1994). …”
Section: Motorised Extreme Sportsmentioning
confidence: 99%
“…Several studies have shown that there is a delay between trampling impact and vegetation decline and long-term data is required for appropriate management of areas receiving sustained recreation use (Cole, 1987). Kutiel et al (2000) and Tzatzanis et al (2003) stated that the low intensity human impact can be alleviated by careful planning of access paths to avoid excessive trampling.…”
Section: Discussionmentioning
confidence: 99%